PERHITUNGAN BEBAN PENDINGINAN PADA SISTEM REFRIGERASI AIR BLAST FREEZER - Boby Wisely Ziliwu (Jurnal Teknologi Terapan, 2020)
Refrigeration is an attempt to maintain the temperature level of a material or room at a level lower than the temperature of the surrounding environment by absorbing heat from the material or room. In short it can be said that refrigeration is the process of transferring heat from a material or another room. Basically, refrigeration technology is heat treatment. The refrigeration process is inseparable from the cooling load problem during the refrigeration machine operates. Excessive cooling load on a refrigeration unit will certainly have an effect that can accelerate the process of decomposition or deterioration in the quality of the catch. This research aims to calculate the cooling load of the blast freezer water and determine the refrigeration components of the blast freezer water unit. From the research results obtained, that the ship whose refrigeration system has a cooling power of 30 kW is able to cool fish as much as 3.5 tons (3,500 kg). With a cooling load of 1 ABF space of 28.54 kW with a fish mass of 3,500 kg. the COPactual achieved by the blast freezer water is about 2.8 smaller than the COPcarnot of 6.1.